Correlation of dermatoglyphics and different types of Skeletal growth pattern - Sushma Sonawane,; Sameer Narkhede,; Karthick Shetty,; Priyanka C Mishra,; Vignesh Kadam,; Rakesh A Singh, (The Bioscan, 2025)
Dermatoglyphics is the study of the distinct pattern found on the palms, soles, fingers, and toes of the human body. In a number of disciplines, including genetics, anthropology, and forensic medicine, these dermatoglyphics have been very significant. According to Sir Francis Galton, a person's dermal pattern does not change over the course of their lifetime. Numerous investigations have raised the possibility of a connection between occlusion and dermatoglyphics. Research has indicated that dermatoglyphics may serve as a useful instrument for determining the underlying skeletal malocclusion. The genetic information in the dermal pattern may be utilized to evaluate the various forms of skeletal malocclusions since the dermal pattern and oral structures grow together. Therefore, the study aims to assess and compare the relationship between dermatoglyphics and skeletal growth pattern. Fifty samples in all were collected, with twenty-five samples each going into the horizontal and vertical growth patterns. The evaluation involved examining the dermatoglyphic pattern, which included loops, whorls, and arches, on the fingers of right and left hands. The Shapiro-Wilk and Kolmogorov-Smirnov tests were used to assess the data. The dermatoglyphic pattern and its relationship with horizontal and vertical growth pattern were statistically significantly correlated.